Agrobiodiversity endangered by sugarcane farming in Mumias and Nzoia sugarbelts of Western Kenya - Netondo, Godfrey Wafula; Waswa, Fuchaka; Maina, Lucy; Naisiko, Tabitha; Masayi, Nelly; Ngaira, Josephine K (Academic Journals, 2014)
Commercial sugarcane farming has been practised in western Kenya for nearly forty years. This monocultural land use is associated with loss of natural vegetation and cropland, thus undermining food security status of a place. Further, sugarcane farming is a major contributor to loss of biodiversity in western Kenya. This study was therefore aimed at determining the long-term effects of sugarcane farming on indigenous food crops and vegetables in Mumias and Nzoia sugarbelts of western Kenya. Up to 188 respondents in three divisions of Mumias and 178 respondents of three divisions in Nzoia were purposively selected. These included small-scale and large-scale farmers. Data were collected using questionnaires, Participatory Rural Appraisal tool, interviews and field observations. Secondary data were obtained from documented materials. Land under indigenous food crops and vegetable has been declining since the introduction of sugarcane. Indigenous food crops and vegetable cultivation by farmers in the sugarbelts has been declining. Furthermore, some farmers have abandoned the growing of these crops altogether. Our results imply that sugarcane farming is a major contributor to agrobiodiversity erosion, but that there are also other important reasons such as change of consumer preference, land fragmentation, climate variability among others. In order to curb further loss of biodiversity, efforts should particularly focus on food crops and livelihood diversification and adoption of farming technologies such as agroforestry
Keywords: Biodiversity; Farming; Indigenous crops; Monoculture; Western Kenya.